Clinical frailty scale as a point of care prognostic indicator of mortality in COVID-19: a systematic review and meta-analysis. (June 2021) - Kastora, Stavroula; Kounidas, Georgios; Perrott, Sarah; Carter, Ben; Hewitt, Jonathan; Myint, Phyo Kyaw
Abstract: Background: COVID-19 has resulted in the largest pandemic experienced since 1918, accounting for over 2 million deaths globally. Frail and older people are at the highest risk of mortality. The main objective of the present research was to quantify the impact of clinical frailty scale (CFS) by increasing severity of frailty and to identify other personal prognostic factors associated with increased mortality from COVID-19. Methods: This study offers a contemporary systematic review and meta-analysis to analyse the stratified mortality risk by increasing CFS sub-categories (1–3, 4–5 and 6–9). Databases searched included EMBASE, MEDLINE, CAB Abstracts, PsychInfo, and Web of Science with end-search restriction the 18th December 2020. Publications identified via MedRevix were followed up on the 23rd March 2021 in peer-reviewed database search, and citations were updated as published. Prospective and retrospective cohort studies which reported the association between CFS and COVID-19 mortality were included. Thirty-four studies were eligible for systematic review and seventeen for meta-analysis, with 81–87% (I 2 ) heterogeneity. Findings: All studies [N: 34] included patients from a hospital setting, comprising a total of 18, 042 patients with mean age 72.8 (Min: 56; Max: 86). The CFS 4–5 patient group had significantly increased mortality when compared to patients with CFS 1–3 [(RE) OR 1.95 (1.32 (95% CI), 2.87 (95% CI)); I 2 81%; p  = 0.0008]. Furthermore, CFS 6–9 patient group displayed an even more noticeable mortality increase when compared to patients with CFS 1–3 [(RE) OR 3.09 (2.03, 4.71); I 2 87%; p <0.0001]. Generic inverse variance analysis of adjusted hazard ratio among included studies highlighted that CFS ( p  = 0.0001), male gender ( p  = 0.0009), National Early Warning Score ( p  = 0.0001), Ischaemic Heart Disease (IHD) ( p  = 0.07), Hypertension (HT) ( p <0.0001), and Chronic Kidney Disease (CKD) ( p  = 0.0009) were associated with increased COVID-19 mortality. Interpretation: Our findings suggest a differential stratification of CFS scores in the context of COVID-19 infection, in which CFS 1–3 patients may be considered at lower risk, CFS 4–5 at moderate risk, and CFS 6–9 at high risk of mortality regardless of age. Overall, our study not only aims to alert clinicians of the value of CFS scores, but also highlight the multiple dimensions to consider such as age, gender and co-morbidities, even among moderately frail patients in relation to COVID-19 mortality. Funding: None.